ANXIETY AMONG SECONDARY SCHOOL ADOLESCENTS OF BHARATPUR METROPOLITAN CITY, CHITWAN - Pokharel, Sonia; Chapagain, Shakuntala; Shrestha, Sumnima (Journal of Chitwan Medical College, 2022)
Background: Anxiety is increasing global problem, but usually hidden from the public view. The objective of this study was to assess prevalence of anxiety among secondary school adolescents in Bharatpur Metropolitan City. Methods: A cross-sectional study was conducted in the Bharatpur Metropolitan City. Systematic sampling technique was used to select 388 higher secondary school adolescents of grade 11 and 12. Data were collected from 18 January 2021 to 14 February 2021 using self administered questionnaire. Validated Nepali version of Beck’s Anxiety Inventory was used for measuring the level of Anxiety. Data entry and analysis were done by IBM SPSS version 20 using descriptive and inferential statistics. Chi square test was used to find the association of Anxiety with independent variables. Results: Among total participants, 30.7% had anxiety symptoms in which 19.9 % had mild anxiety, 7.6% had moderate anxiety and 3.2% had severe anxiety. Marital status of parents (p= <0.001), ongoing health problems (<0.001), history of mental illness (p=<0.001), marital status (p=0.04) and gender p=0.015) of respondent were found to have association with anxiety. Conclusions: Study concluded that nearly one third of participant had reported to experienced anxiety disorder. Thus local government and school authority needs to pay special attention in addressing anxiety among adolescents by formulating different program and policies for school going adolescents in local level.